2008
DOI: 10.2137/145960608786118767
|View full text |Cite
|
Sign up to set email alerts
|

Plant biotechnology for deeper understanding, wider use and further development of agricultural and horticultural crops

Abstract: Plants bind solar energy to organic matter via photosynthesis and assimilation of carbon dioxide from the atmosphere and comprise the major source of nutrition and bioenergy. Plant biotechnology contributes to solution of important constraints in food and feed production and creates new technologies and applications for the sustainable use of plant resources. Genome-wide approaches such as massive parallel sequencing and microarrays to study gene expression, molecular markers for selection of important traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 132 publications
1
0
0
Order By: Relevance
“…However, is it that the more waste amendments added, the greater the accumulation of organic carbon? The results of this study indicated that waste amendments did significantly affect the SOC content, which was consistent with previous research results [20,21]. The main reason is that the input of waste amendments changes the basic C/N of soil and the life activities of microorganisms and then produces the binders and carriers that cause the formation of soil aggregates and increase the number of soil aggregates, improving the stability of the agglomerates, which will improve the stability of POC and be conducive to soil carbon [22,23].This study also showed that the SOC of amendment addition treatments gradually increased with increasing amounts of amendment.…”
Section: Discussionsupporting
confidence: 93%
“…However, is it that the more waste amendments added, the greater the accumulation of organic carbon? The results of this study indicated that waste amendments did significantly affect the SOC content, which was consistent with previous research results [20,21]. The main reason is that the input of waste amendments changes the basic C/N of soil and the life activities of microorganisms and then produces the binders and carriers that cause the formation of soil aggregates and increase the number of soil aggregates, improving the stability of the agglomerates, which will improve the stability of POC and be conducive to soil carbon [22,23].This study also showed that the SOC of amendment addition treatments gradually increased with increasing amounts of amendment.…”
Section: Discussionsupporting
confidence: 93%